PENGARUH STRES KERJA, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA PT. PLN (PERSERO) PUSAT MANAGEMENT PROYEK SEMARANG - Siska, Willy; Su’un, Muhammad; Wahid, Muhsin (AkMen JURNAL ILMIAH, 2025)
This study aims to examine the effects of Work Stress, Job Satisfaction, and Organizational Commitment on Employee Performance at PT. PLN (Persero) Central Project Management Semarang. The data for this study were obtained from employees at PT. PLN (Persero) Central Project Management Semarang in 2025 who agreed to be respondents. This research used primary data collected through direct field research by distributing questionnaires/statements to the respondents. Sampling was conducted using a census method due to the small sample size, where the sample consisted of the entire population of 90 employees. Data analysis techniques involved descriptive statistical analysis and SPSS version 26.0. The results indicate that work stress has a significant negative effect on employee performance, where excessive stress can reduce concentration, health, and productivity. Furthermore, job satisfaction influenced by job suitability, salary, and relationship with supervisors plays an important role in enhancing work motivation. Additionally, organizational commitment has a positive and significant effect on performance, as committed employees demonstrate responsibility, loyalty, and maximum effort toward the company’s success. Therefore, managing work stress, improving job satisfaction, and strengthening commitment are key factors in enhancing employee performance.